Assessment of water quality of the Halda River using multiple WQI approaches: Implications for Riverine Ecosystem and Sustainable Management - Ahasanul Karim; Muhammad Towhid Moula; Ranjit K. Nath; Masud Rana Rashel; Mh. Mosfeka Chowdhury; Abu Mansur; Md. Masudur Rhaman; Mayeen Uddin Khandaker (PLoS ONE, 2026)
The Halda River-Bangladesh’s only natural breeding ground for major carps and a vital freshwater resource is undergoing alarming deterioration in water quality. This study assessed its ecological condition by applying seven Water Quality Indices (WQIs): Weighted Arithmetic, British Columbia, Canadian, Malaysian, Oregon, Assigned, and the recently developed Method of the Removal Effects of Criteria (MEREC-WQI). To record the seasonal and regional changes, surface water samples were collected during both dry and wet seasons. It has been observed that the respective values of several important parameters like turbidity, ammonia, biochemical oxygen demand (BOD₅), and dissolved oxygen (DO), often exceeded national reference limits or guidelines. The deduced water quality index (WQI) scores ranged from 25 to 45, which categorized the river water as ‘poor’ to ‘very poor’. The water quality shows more deterioration during the dry season, which might be related to the reduction of water flow, industrial discharges, etc. Overall, the uses of various WQI techniques help to obtain a comprehensive and comparative assessment of river health. This study indicates a non-negligible man made stress on the Halda River ecosystem, and it recommends to implement a comprehensive pollution control strategies and viable watershed management to protect the River’s ecological balance.